2020
DOI: 10.3390/en13081979
|View full text |Cite
|
Sign up to set email alerts
|

Combining Artificial Intelligence with Physics-Based Methods for Probabilistic Renewable Energy Forecasting

Abstract: A modern renewable energy forecasting system blends physical models with artificial intelligence to aid in system operation and grid integration. This paper describes such a system being developed for the Shagaya Renewable Energy Park, which is being developed by the State of Kuwait. The park contains wind turbines, photovoltaic panels, and concentrated solar renewable energy technologies with storage capabilities. The fully operational Kuwait Renewable Energy Prediction System (KREPS) employs artificial intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…These data requirements are not dissimilar to those of statistical methods such as MOS. For dynamic methods such as DICast that are retrained frequently, less data may be required to produce optimal results—DICast can be optimized with 90 days of data or less [ 15 , 20 ]. The computational time for these methods is trivial in comparison with the time to accomplish the NWP simulations.…”
Section: Emergence Of Ai Post-processing—a Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These data requirements are not dissimilar to those of statistical methods such as MOS. For dynamic methods such as DICast that are retrained frequently, less data may be required to produce optimal results—DICast can be optimized with 90 days of data or less [ 15 , 20 ]. The computational time for these methods is trivial in comparison with the time to accomplish the NWP simulations.…”
Section: Emergence Of Ai Post-processing—a Brief Literature Reviewmentioning
confidence: 99%
“…Figure 1 demonstrates the DICast post-processing methodology, which is representative of the many other systems currently being used. DICast has evolved over time to include additional machine-learning methods and has been shown to dramatically improve forecasts across multiple weather-dependent applications including road conditions [16], precision agriculture, wind and solar energy [17][18][19][20], among others. Now, many commercial weather companies and national centres employ AI-based post-processing methods [21].…”
Section: (A) Forecast Improvements With Aimentioning
confidence: 99%
“…In a related study in the context of wind energy, Phipps et al (2020) find that a two-step strategy of post-processing both wind and power ensemble forecasts performs best and that the calibration of the power predictions constitutes a crucial step. Ideally, statistical post-processing of solar irradiance forecasts could contribute an important component to modern, fully integrated renewable energy forecasting systems (see e.g., Haupt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that ML-based models outperform conventional statistical methods (i.e., time series approaches) in which the inputs are based on time series data from measurements [5][6][7][8]. It is known that, with the increase of time horizon, the inclusion of NWP inputs becomes more and more important, especially for time horizons longer than 6 h. In recent years, research works on developing NWP+ML models for wind power forecasting have emerged [9][10][11][12][13][14][15][16]. Mostly, the role of ML can be regarded as statistical downscaling, which downscale NWP results into power through a transfer function trained with historical data.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [16] describes an integrated wind and solar energy forecasting system which is developed for the Shagaya Renewable Energy Park in Kuwait by blending physical models with artificial intelligence. Testing results showed that the normalized RMSE for wind power forecasts at horizons between 12 and 24 h is about 20%.…”
Section: Introductionmentioning
confidence: 99%